Microemulsion-mediated synthesis of sedum rubrotinctum shaped Cu2O architecture with efficient sunlight driven photocatalytic activity. Issue 2 (22nd December 2015) - Yang, Lu-feng; Chu, De-qing; Wang, Li-min; Ge, Ge; Sun, Hui-lou
Abstract : Schematic of photo-activation of sedum rubrotinctum shaped Cu2 O photocatalyst and degradation of MB. Abstract : A novel Cu2 O sedum rubrotinctum shaped architecture has been successfully synthesized in a water/oil (w/o) microemulsion. The obtained Cu2 O sample was evaluated for its ability in the degradation of methylene blue under sunlight irradiation. It was found that a degradation of 98.94% was achieved in 90 min irradiation time.